Análise de estruturas laminares pelo Método da Energia Discretizada - Pletz, Everaldo (1983)
This work presents the Discrete Energy Method whose formulation is based on energy principles through a special form of finite differences. It does not depend on the boundary conditions and uses the concept of matrix of elements in which the structures are discretized. The objective of this work is the analysis of plates using cylindrical coordinates, subjected to loads belonging or not to their planes with the small displacements assumption, and of plates with geometrically non-linear response by means of the Discrete Energy Method. The results of the analysis of several structures subjected to various types of loading with different elastic properties and boundary conditions are presented. These results are compared with others obtained from experimental or theoretical analysis or by means of other numerical methods.